Consequences of trisomy syndromes: 21 and beyond - Krivega, Maria; Storchová, Zuzana (Trends in genetics, 2023)
The mechanisms underlying pathologies in Down syndrome remain poorly understood. In this forum article we compare the cellular phenotypes of chromosome 21 trisomy with other trisomic cells. We argue that both effects of the extra chromosome 21 and the global consequences of chromosome gain must be considered to understand complex pathologies of Down syndrome.